Identifikasi dan penataan Kawasan Agrowisata Salak Pondoh Bangunkerto kecamatan Turi Sleman. - Tri Haryanto (Agro 14 UMY 028, 2014)
*28 The Research entitled of Identification and arrangement Salak Pondoh Agrotourism in Bangunkerto, Turi District, Sleman has been done from August to November 2013. It's aimed to identify and to arrange biophysical conditions in Salak Pondoh Agrotourism to increase the number of visitors and provide prosperity to communities around the area. This research used Survey method, which is done by observation and questionnaires. The Data were analyzed with descriptive and spatial method. The data types divided into two group, primary data and secondary data. Primary data includes the user perception of Salak Pondoh Agrotourism, while secondary data includes maps, geographic location, soil type, topography, climate and social condition of the communities around Salak Pondoh Agrotourism. The results showed that facility of Salak Pondoh Agrotourism in Bangunkerto damaged which includes swiming pool, playground, shack, view post, and bridge pond. re-Planning salak pondoh agrotourism by adding some facilities and attractions such as restaurants, souvenir shop, cafeteria, nursery, and place outbound. Keyword : Identification, Lanscape Planning, Salak Pondoh Agrotourism